Problems and approaches (With 91 figures) (New York, 1988)
The book conveys an up-to-date overview of the science of ecotoxicology, which describes and predicts ecological changes resulting from a variety of human activities involving release of xenobiotic and other chemicals to the environment. The book also guides through the field starting with a discussion of contemporary concepts and issues and proceeding to a review of the response of ecosystems to chemical stress, examples of methods amd models, and finally to ecological approaches to risk assessment and management
Keywords: pollution - environmental aspects